Crime in Ireland since the Second World War - Brewer, John; Lockhart, William H.; Rodgers, Paula (Statistical and Social Inquiry Society of Ireland, 1996)
Over two decades of terrorism have given Northern Ireland the image of being a violent, crime-torn country. Belfast is associated in imagery with the bomb and the bullet, with Beirut and Bosnia and all other alliterations for social breakdown and dislocation. People with greater acquaintance of Northern Ireland, however, have noted its relative peacefulness. In reference to such, people comment on its low crime rate. In these ways, crime levels are held up as testimony against images of a buffeted, battle-weary Northern Irish populace. Ordinary crime levels in Northern Ireland throw up deep issues for empirical investigation and theoretical consideration. Moreover, Northern Ireland sits at the fulcrum of Great Britain and the Irish Republic and a study of ordinary crime there permits a comparative framework to cover crime trends elsewhere in the British Isles, particularly the Irish Republic, about which so little is known compared to the wealth of material on crime in Great Britain.
Read before the Society, 15 February 1996
Keywords: Crime rate; Irish crime; 314.15